2018
DOI: 10.1108/ijwbr-01-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Winery website loyalty: the role of sales promotion and service attributes

Abstract: Purpose This paper aims to examine the relationship between feelings toward buying wine on mobile phones and m-commerce website loyalty by examining the mediating role of sales promotion and the moderating role of service attributes of the m-commerce websites in influencing the mediation. Design/methodology/approach A total of 3,318 completed surveys were collected. Drawing on a large non-probability criterion-based purposive sample across six countries (France, Germany, Greece, South Africa, USA and Canada)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…In this new scenario, being aware of what web users say in their online conversations when they talk about wine is becoming very important for wine producers, and online social media represent a new channel of communication to take into consideration [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this new scenario, being aware of what web users say in their online conversations when they talk about wine is becoming very important for wine producers, and online social media represent a new channel of communication to take into consideration [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ahrholdt et al (2017) stressed the role of the quality-delight-loyalty system and found that the predicted relationship is possible and that customer delight poses a significant positive mediating effect between service quality and customer loyalty. On the other hand, Pelet et al (2018) analyzed the mediating impact of promotional offers between website loyalty and buying behavior and found a significant positive mediating effect of promotional offers between the two variables. Similarly, Lee and Chen-Yu (2018) analyzed the mediating effect of price discounts on perceived quality and perceived value of consumers' perception towards apparel products and they found a significant mediating role of price discounts.…”
Section: Mediation Effectsmentioning
confidence: 99%
“…There is also a substantial body of work that has examined similar questions for still wines (e.g., see Hussain et al, 2007;Kerr et al, 2004;Pickering et al, 2014). Overall, there is evidence that U.S. wines sales (and, notably, U.S. sparkling wines sales) have been driven, in part, by increased product availability from domestic producers and imports, increased marketing and promotion efforts for wines and wine regions (Pelet et al, 2018), a greater prevalence of expert ratings in the marketplace (Hilger et al, 2011), and an increasingly sophisticated consumer base in the United States (Hisano, 2017).…”
Section: Introductionmentioning
confidence: 99%